Carbon nanospheres induced high negative permittivity in nanosilver-polydopamine metacomposites. (June 2019) - Gu, Hongbo; Xu, Xiaojiang; Dong, Mengyao; Xie, Peitao; Shao, Qian; Fan, Runhua; Liu, Chuntai; Wu, Shide; Wei, Renbo; Guo, Zhanhu
Abstract: In this work, a unique high negative permittivity is observed in the carbon nanosphere (CNS) supported nanosilver-polydopamine (PDA) metacomposites (called CNS-PDA/Ag). The CNS possesses a uniform spherical structure (average diameter of about 200 nm) with a bridge to link CNS together. The Ag nanoparticles are observed to be uniformly deposited on the surface of CNS-PDA core-shell structures with an average diameter of around 10–20 nm. Both impedance and optical band gap results confirm that the CNS-PDA/Ag metacomposites can form a conductive network pathway for further improving their electrical conductivity (about 1 and 2 magnitudes higher than that of CNS and CNS-PDA, respectively). With the support of CNS, the enhanced high negative permittivity observed in the CNS-PDA/Ag metacomposites (about −6.1 × 10 5 ) compared with CNS (around −1.2 × 10 5 ), CNS-PDA (around 2.5 × 10 4 ), and PDA/Ag (around 2.0) is ascribed to uniform decoration of PDA and Ag nanoparticles, induced electric dipole polarization, excellent electrical conductivity as well as anisotropy in dielectric and electrical properties of CNS, PDA, and Ag. The negative permittivity and positive reactance demonstrate an inductance character of the CNS-PDA/Ag metacomposites. This work opens up a new strategy for design and development of metacomposites. Graphical abstract: Image 1